Environmental Niche Modelling with Desktop GARP for Wild Origanum vulgare L . (Lamiaceae) in Armenia (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Predicting species’ distributions has became one of the significant components of conservation biology in recent years. During the study, GARP (genetic algorithm) has been identified the key modelling technique for determining Origanum vulgare L. (Oregano, Lamiaceae) environmental niche in the Republic of Armenia. For over three consecutive years, from 2010-2013 it has been created relevant environmental layers through ESRI ArcGIS programs to be used with the plant actual distribution (occurrence records) as input data of GARP. In the result of the study, it has been produced the fundamental and realized niche and predictive habitat distribution of O. vulgare L. with Bitmap under the global climate change. Produced Bitmap illustrates that Oregano distributions would decrease mostly in the central regions due to environmental deterioration and climate change. This research could provide significant data for future conservation planning of wild Oregano in the Republic of Armenia.